2013
DOI: 10.1371/journal.pone.0078266
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Sociodemographic Factors Associated with Asthma Related Outcomes in Early Childhood: The Generation R Study

Abstract: RationaleFew studies have analyzed the association of socioeconomic and sociodemographic factors with asthma related outcomes in early childhood, including Fraction of exhaled Nitric Oxide (FeNO) and airway resistance (Rint). We examined the association of socioeconomic and sociodemographic factors with wheezing, asthma, FeNO and Rint at age 6 years. Additionally, the role of potential mediating factors was studied.MethodsThe study included 6717 children participating in The Generation R Study, a prospective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Nineteen met the inclusion criteria (Figure ) . For the three studies that overlapped data were kindly supplied by the authors . In addition, a further author kindly supplied their data so the study could be included .…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen met the inclusion criteria (Figure ) . For the three studies that overlapped data were kindly supplied by the authors . In addition, a further author kindly supplied their data so the study could be included .…”
Section: Resultsmentioning
confidence: 99%
“…the cumulative asthma incidence is lower in girls as compared to boys raised on a farm [18]. Asthma in early childhood is generally associated with male gender, poor socioeconomic status, and exposure to soot, exhaust and/or household tobacco, wood, or oil smoke [19, 20]. Yet, asthma in early childhood is only associated with obesity in young girls, not in young boys in two large cross-sectional series from China and the Netherlands [21, 22], and in two longitudinal cohorts from the United Kingdom and Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Data have suggested that antibiotics in utero may change the maternal or placental microbiome and increase the child’s risk of developing allergic disease 13,14 . Factors that modify microbial exposure pre- and perinatally may have a long-term impact on the risk of developing subsequent atopic disease 7,15,16 . Research utilizing prospective birth cohorts has been limited, especially among impoverished urban residents.…”
Section: Introductionmentioning
confidence: 99%